Effect of Particle Size of Rice-Husk Derived Silica on the Pyrolysis of Pomelo Peels - Karakate Bo-ongcharoenlab; Iyarin Tongdang; Worapon Kiatkittipong; Adisak Jaturapiree; Kanjarat Sukrat; Thanunya Saowapark; Ekrachan Chaichana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Silica with two different sizes i.e. microsilica (MS) and nanosilica (NS) was used as a catalytic support for vanadium (5-15 wt%) in the pyrolysis of pomelo peels. Besides use of pomelo peels (agricultural residues) as a feedstock for the pyrolysis, to contribute to environmental sustainability, rice husk was used as a silica source for obtaining the silica support. From the result, it was found that non-catalytic pyrolysis of pomelo peels gave a bio-oil yield of 33.3 wt%. The catalytic pyrolysis with vanadium-modified silica decreased the bio-oil yields ranging between 27.2-33.1 wt%. This was due to the occurrence of the second reactions generated from the active sites on the catalysts, which leads to the conversion of bio-oil into gas products. For NS catalyst, increasing the amount of vanadium loading directly decreased the bio-oil yields and increased the gas yield. The variation of product phase distribution was not clearly observed for MS catalyst even with various vanadium loadings. In addition, NS catalyst exhibited higher efficiency in reducing the acid content in the bio-oil, and increasing the phenol content. The distinguished properties of the nanoparticles may be the main reason for these phenomena. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).